2003
DOI: 10.1001/jama.290.5.603
|View full text |Cite
|
Sign up to set email alerts
|

A Mental Health Intervention for Schoolchildren Exposed to Violence

Abstract: N THE LAST DECADE, THERE HAS BEEN heightened awareness of the extent to which children personally witness or experience violence. [1][2][3] Public health officials have responded by identifying violence as one of the most significant US public health issues. [4][5][6] Large numbers of US children experience such violence, and an even greater number may experience symptoms of distress after personally witnessing violence directed at others. 2,7-9 For many children, personally experiencing or directly witnessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
401
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(425 citation statements)
references
References 61 publications
16
401
2
3
Order By: Relevance
“…Fewer studies have been published on the effectiveness of cognitive behavioural treatment for children with PTSD (e.g. Cohen, Deblinger, Mannorino, & Steer, 2004;Cohen, Mannarino, & Staron, 2006;Deblinger, Lippman, & Steer, 1996;King et al, 2000;Smith et al, 2007;Stein et al, 2003; for review see Silverman et al, 2008). These studies show that cognitive behavioural treatment is more effective than a waitlist control condition, community treatment, supportive therapy or child-centred therapy on short-and long-term outcome measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer studies have been published on the effectiveness of cognitive behavioural treatment for children with PTSD (e.g. Cohen, Deblinger, Mannorino, & Steer, 2004;Cohen, Mannarino, & Staron, 2006;Deblinger, Lippman, & Steer, 1996;King et al, 2000;Smith et al, 2007;Stein et al, 2003; for review see Silverman et al, 2008). These studies show that cognitive behavioural treatment is more effective than a waitlist control condition, community treatment, supportive therapy or child-centred therapy on short-and long-term outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Most treatment studies included children displaying traumatic symptoms after being exposed to one specifi c type of trauma, such as sexual assault (e.g. Cohen et al, 2004;Deblinger et al, 1996;King et al, 2000; for review see Silverman et al, 2008), violence (Stein et al, 2003), or the death of a parent or loved one .…”
Section: Introductionmentioning
confidence: 99%
“…Trauma-focused CBT has been shown with randomized controlled trials (RCT) to be effective in treating PTSD in sexually abused children and adolescents (Celano & Rothbaum, 2002;Cohen, Deblinger, Mannarino, & Steer, 2004;King, Tonge, Mullen, Myerson, Heyne, Rollings, et al, 2000;Pine & Cohen, 2002). Another RCT has shown CBT effectiveness as a group intervention for schoolchildren exposed to violence (Stein, Jaycox, Kataoka, Wong, Tu, Elliot, et al, 2003), while a similar study demonstrated the efficacy of group CBT for treating PTSD in Latino immigrant children exposed to community violence (Kataoka, Stein, Jaycox, Wong, Escudero, Tu, et al, 2003).…”
Section: Behavioral Cognitive Behavioral and Interpersonal Therapiesmentioning
confidence: 99%
“…CBITS has been applied to two major studies in children exposed to violence in the community. In the study by Stein et al (2003), CBITS was superior to the waiting list in reducing PTSD and depression cases.Several other CBT protocols have been found, embodying promising practices that could facilitate the application of CBT to special populations of different origins and specificities in symptomatology. For example, UCLA Τrauma and Grief Component Therapy has been primarily provided in schools, showing a benefit to teenagers exposed to war, community violence or even terrorist acts.…”
mentioning
confidence: 95%
“…CBITS has been applied to two major studies in children exposed to violence in the community. In the study by Stein et al (2003), CBITS was superior to the waiting list in reducing PTSD and depression cases.…”
mentioning
confidence: 95%